Poco-poco implementation of the death penalty for corruptors in the time of force majeure - Amalia Syauket; Erwin Owan Hermansyah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Under the legal basis, a pandemic is included in the time of force majeure, "extraordinary" time, or disaster time. In such a situation, the crimes committed will be threatened with heavier punishments than in normal situations. However, the reality that appears until 2021, the heaviest punishment ever imposed in a corruption case is a life sentence. This study aims to find out what causes the ambiguity of the judge's imposition of the death penalty for corruptors during force majeure. With a qualitative approach, the author concludes that in positive Indonesian law there is still the threat of the death penalty for perpetrators of crimes, such as crimes of corruption, especially in certain circumstances. The reason why the judges are ambiguous in imposing the death penalty for corruptors is because the loss to the state which is also the loss of the people has not yet become a feeling of justice. Thus, the death penalty in corruption cases is rarely even never applied so that the judge is giddy, not firm in enforcing the threat of punishment in this case. Novelty of this research, it is necessary to develop efforts to impose the Social Costs of Corruption.